The sociological sciences and sexual ethics - Dagmang, Ferdinand D. (2006)
This study deals with sexual ethics' relationship with sociological studies on sexuality. The social setting is seen as a component of every ethical scrutiny, even if the latter deals with a cause of failure or deficiency in individual moral choice. Conscious decisions and actions, wchich are tacitly determined by what have preceded individual choice, are no longer the only important object of ethical argumentation. Since choice is circumscribed by objective determinants, the latter seems to be a focal point, if not an indispensable focal point, of every ethical analysis. The present study also offers a brief exploration of the social sciences' examination of sexuality, and includes an example of when Sociology encounters moral problems. An approach to formulating sexual-ethical propositions is shown as social scientists and ethicists take into account the socio-cultural conditions of sexual attitude and behavior.
Keywords: Sexual ethics